Prácticas espirituales: ritual, armonización y círculos de la palabra, una propuesta curricular desde la educación propia (2022)
For indigenous communities, one of the pillars of their own education is spirituality, understood as the harmonious human-nature relationship that is currently fractured and oriented towards only religious or only indigenous tendencies, ignoring its true inclusive, non-discriminatory value. Consequently, it is necessary to understand the configured meanings of spiritual practices: ritual, harmonization and circles of the word, to reconfigure the curricular frameworks of educational institutions. This qualitative research reflects on the importance of articulating spirituality to the teaching and learning process, and its main objectives are to characterize, identify and reconfigure spiritual practices as a proposal for self-education with a participatory action research (PAR) approach. It is contrasted with authors and the voices of the researcher and those investigated; where this category emerges: “the warp of spirituality, weaving education.” It is concluded that spirituality advocates all life processes and must be managed transversally in educational and curricular terms.